Konsep Pendidikan Generasi Anak Shalih (Analisis Buku Mendidik Anak Bersama Nabi Karya Muhammad Nur Abdul Suwaid) - Surono, Surono; Prahastiwi, Eka Danik; Suprayitno, Kabul (Lembaga Yasin AlSys, 2022)
Parenting is a behavior or way that parents do in educating their children. Children are safe and it is the responsibility of parents to be educated and cared for as well as possible. It is parents who will determine the development and future of children later. Parents can imitate the parenting applied by the Prophet Muhammad. He is a messenger of Allah SWT, a role model and a concrete example in educating Islamic children. One of the books that examines the upbringing of the Prophet Muhammad is the book Educating with the Prophet Saw by Muhammad Nur Abdul Hafizh Suwaid. The purpose of this research is to reveal the upbringing of the Prophet Muhammad in the book Educating Children with the Prophet SAW Mendidik. The type of research that the author uses in this research is library research library research. In the process of data analysis techniques the author uses document analysis. The results showed that the method of educating children like Rasulullah SAW contained in the book Mendidik Bersama Nabi SAW by Muhammad Nur Abdul Hafizh Suwaid that can be followed includes good examples, the right time to provide guidance, Being fair and equal to children, Fulfilling rights Children, Pray for children, Buy children's toys, Help children to do good and obey, Do not criticize children.